Bank productivity in China 1997 - 2007: An exercise in measurement - Kent Matthews; Nina Zhang (Cardiff University, Cardiff Business School, 2009)
This study examines the productivity growth of the nationwide banks of China and a sample of city commercial, banks for the eleven years to 2007. Estimates of total factor productivity growth are constructed with appropriate confidence intervals, using a bootstrap method for the Malmquist index. The study adjusts for the quality of the output by accounting for the non-performing loans on the balance sheets of the banks and tests for the robustness of the results by examining alternative sets of outputs. The productivity growth of the state-owned commercial banks (SOCBs) is compared with the joint-stock banks (JSCBs) and city commercial banks (CCBs). The results show that average total factor productivity for the joint-stock banks was better than that of the state-owned banks for some models of measurement but not others. But the average city commercial banks improved its productivity growth both in terms of frontier shift and efficiency gain throughout the whole period. The study also shows that individual state-owned and joint-stock banks did improve their productivity growth and defined an improving production frontier. Most other banks lagged behind so that the gap between the inefficient banks and the most efficient banks widened. While individual banks improved their productivity growth there is no evidence that the average productivity growth of Chinese banks as a whole improved in the run-up to WTO.
Keywords: D24; G21; 330; Bank Efficiency; Productivity; Malmquist index; Bootstrap; Bank; Bankgeschäft; Produktivität; Messung; China